Acute Lower Respiratory Tract Infection Increased the Risk of Cardiovascular Events and All-Cause Mortality in Elderly Patients With Stable Coronary Artery Disease - Zhao, Xiaoqian; Liu, Yuan; Zhang, Jinping; Fu, Shihui; Song, Chengyun; Bai, Yongyi; Luo, Leiming (Frontiers in Cardiovascular Medicine, 2021)
Objective: To investigate the predictors of acute cardiovascular events within 90 days after an acute lower respiratory tract infection (ALRTI) in elderly patients with stable coronary artery disease (sCAD). Methods: Observational analyses were conducted in a prospective cohort of the elderly with sCAD, during 90 days after they were hospitalized for ALRTI. Multiple logistic regression analysis was performed to identify predictors for acute cardiovascular events and all-cause mortality. Results: The present study comprised 426 patients with sCAD (median age: 88 years; IQR: 84–91; range: 72–102). Among these patients, 257 suffering from ALRTI were enrolled in the infection group. Meanwhile, 169 patients who did not suffer from ALRTI were regarded as the non-infection group. Compared with the non-infection group, patients in the infection group had a higher incidence of acute cardiovascular events (31.9 vs. 13.6%, p < 0.001) and all-cause mortality (13.2 vs. 1.8%, p < 0.001) during the 90-day follow-up. In addition, in the infection group, the incidence of cardiovascular events was also higher than those in the non-infection group during the 7-day and 30-day follow-up (10.9 vs. 2.4%, p = 0.001; 20.6 vs. 6.5%, p < 0.001). The same difference in the incidence of all-cause mortality during 7 and 30 days (1.2 vs. 0%, p = 0.028; 3.9 vs. 0.6%, p = 0.021) was observed between the two groups. Furthermore, multiple regression analysis found that ALRTI was independently associated with increased risk of cardiovascular events and all-cause mortality in elderly patients with sCAD. Conclusion: In elderly patients with sCAD, ALRTI was an independent predictor for both cardiovascular events and all-cause mortality.